2017
DOI: 10.18393/ejss.319208
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of soil organic carbon using VIS-NIR spectroscopy: Application to Red Mediterranean soils from Croatia

Abstract: The objectives of this research were: (i) to assess the accuracy of diffuse reflectance spectroscopy (DRS) in predicting the soil organic carbon (SOC) content, and (ii) determine the importance of wavelength ranges and specific wavelengths in the SOC prediction model. The reflectance spectra of a total of 424 topsoils (0-25 cm) samples were measured in a laboratory using a portable Terra Spec 4 HiRes Mineral Spectrometer with a wavelength range 350-2500 nm. Partial least squares regression (PLSR) with leave-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The both A and B horizon are characterized by a wide range of SOC content. These results correspond to literature findings for Terra rossa soil of Dalmatia, Croatia (Miloš and Bensa, 2017).…”
Section: Description Of Soil Propertiessupporting
confidence: 92%
“…The both A and B horizon are characterized by a wide range of SOC content. These results correspond to literature findings for Terra rossa soil of Dalmatia, Croatia (Miloš and Bensa, 2017).…”
Section: Description Of Soil Propertiessupporting
confidence: 92%
“…(He, et al, 2009) and deposits in the VIS (visible) bands (660, 570 and 410nm) (Viscarra/ Rossel et al, 2006). Typically, soil spectrum characterized with reflectance increasing with increasing wavelengths, the wavelengths contributing most to the prediction of SOC content were between 1050 to 2380 nm (Milos and Bensa 2017). Sun and Niu, (2018) discovered that the spectral curves of the soil with different SOC content grades exhibited a uniform pattern, which increased rapidly in the visible band (400-760 nm), but then ascended gradually in the short NIR and NIR long wave bands (780-1300 nm).…”
Section: Soil Laboratory Analysis Resultsmentioning
confidence: 99%
“…B11 is a single multispectral band that belongs to the short-wave infrared range. Miloš et al [34], Viscarra Rossel and Hicks [35], and Wang et al [36] have reported that the SOM-responsive bands were in the short-wave infrared wavelength range and were dominated by C-H vibrations, kaolinite, soil adsorbed water, and Al-OH clay minerals. In contrast, Liu et al [33] found that the B3 and B6 bands in the visible wavelength range were closely correlated with SOM content of black soils.…”
Section: Using the Band Combination Indices For Characterizing The So...mentioning
confidence: 99%